Evaluation of multi-target immunogenic reagents for the detection of latent and body fluid-contaminated fingermarks. (July 2016) - Lam, Rolanda; Hofstetter, Oliver; Lennard, Chris; Roux, Claude; Spindler, Xanthe
Highlights: Antibody/aptamer immunogenic reagents were designed for fingermark detection. Multiplex reagents were evaluated against and in sequence with current techniques. Current methods outperformed solution-based immunogenic reagents. Sequencing immunogenic reagents did not provide any significant benefit. Immunogenic reagents have potential for specialist and "last resort" application. Abstract: Fingermark enhancement reagents capable of molecular recognition offer a highly selective and sensitive method of detection. Antibodies and aptamers provide a high degree of adaptability for visualisation, allowing for the selection of the most appropriate visualisation wavelength for a particular substrate without the need for specialist equipment or image processing. However, the major hurdle to overcome is the balance between sensitivity and selectivity. Single-target molecular recognition is highly specific, purported to have better detection limits than chemical reactions or stains, and can provide information about the donor or activity, but often results in incomplete ridge pattern development. Consequently, the development and evaluation of multi-target biomolecular reagents for fingermark enhancement was investigated, with the focus on endogenous eccrine secretions. To assess the suitability of the immunogenic reagents for potential operational use, a variety of parameters (i.e., processing time, fixing and working solution conditions) were optimised on a wide range of non-porous and semi-porous substrates. The relative performance of immunogenic reagents was compared to that of routine techniques applied to latent marks and marks in blood, semen and saliva. The incorporation of these novel reagents into routine technique sequences was also investigated. The experimental results indicated that the multi-target immunogenic reagents were not a suitable alternative to routine detection methods or sequences, but may have promise as a "last resort" method for difficult substrates or cases.